Pengaruh Lingkungan Kerja dan Disiplin Kerja terhadap Kinerja Karyawan pada PT Keo San Indonesia - Sifah Fauziah; Syarif Ali; Ediwarman Ediwarman (Penerbit Goodwood, 2020)
Purpose: This research is a quantitative study that aims to determine and prove the effect of work environment and work discipline on employee performance. Research methodology: The sample used in this study were all employees of the production division of PT Keo San Indonesia where the researchers used a saturated sample of 60 employees. The analytical technique used is the path analysis method and data processing is carried out through SmartPLS 3.3.3. Result: The results of the test obtained (1) the work environment has a significant effect on employee performance, (2) work discipline has a significant effect on employee performance. Limitations: Researchers find it difficult to find references for research, because the research was carried out during the Covid-19 pandemic. However, this can be overcome by looking for references online. Contribution: This research is expected to be able to make a comparison between theoretical knowledge and practice applied by PT Keo San Indonesia to the work environment and work discipline that affects the performance of its employees.